Welcome back, Puffin! - Bentley, Dawn; Stover, Beth, 1969-; Smithsonian Institution (Norwalk, CT : Little Soundprints, 2003)
Puffin and her mate fly over the ocean to an island where, each year, they have a baby in the very same burrow.
Keywords: Puffins -- Juvenile fiction